The Application of SWOT-AHP Combination in Small-Medium Enterprises (SMEs): A Literature Review 2010-2020 - Dicinta, Mutiara; Bawono, Baju; Kristyanto, Bernadus (International Journal of Mechanical Engineering Technologies and Applications, 2021)
This study discusses two cases of combined use of SWOT-AHP in SMEs from outside Indonesia. The journals studied were journals published in the last 10 years, namely from 2010-2020. This study explains the combined use of SWOT-AHP abroad and domestically (Indonesia) and further discusses the benefits and challenges in the combined implementation of the SWOT-AHP method in SMEs. This research can be a reference in subsequent studies that apply the combined SWOT-AHP based on the potential and challenges of using the combined SWOT-AHP.